SEMAIL OPHIOLITE SUPRA-SUBDUCTION ZONE SETTING: EVIDENCE FROM SERPENTINITES AND THEIR CHROMITE AT MUNDASSAH AREA, UAE - Mohamed, El Tokhi; Sulaiman, Alaabed; Eldin, Amin, Bahaa (European Scientific Journal, ESJ, 2014)
Serpentinites as the base of the Semail Ophiolite in the northern United Arab Emirates represent a products of hydration of peridotites as a part of the oceanic lithosphere that was obducted onto the Arabian continental margin during the Late Cretaceous. Three main rock types are recognized in the Mundassah area of eastern UAE: 1-Serpentinized peridotites, 2-Massive serpentinites and 3-Foliated serpentinites. At least three stages of serpentinization are recorded in the Mundassah area. The first stage is characterized by the crystallization of blade-shaped lizardite as pseudomorphic replacement of olivine-orthopyroxene. The second stage is worked by the appearance of fibers and dense fine-grained aggregates of chrysotile and antigorite replacing or cutting the lizardite. The third stage involved crystallization of clinochrysotile and carbonate veinlets. Analyses of chromite samples from the Mundassah area show that it has relatively high Cr2O3 (>53 wt%) and low of Fe2O3 (2.9-9.9 wt%) and low TiO2 (< 0.2 wt%). Mundassah chromites are typical of forearc peridotites and are distinctly different from those of oceanic abyssal peridotites. Most serpentinites have high Cr (>2200 ppm), Ni(>2000 ppm) and MgO (>36 wt%), and low Al2O3 (< 2 wt%) and CaO (< 1.5 wt%). Low CaO content may be attributed to the dissolution of clinopyroxene during serpentinization, but very low Al2O3 content of together with high Cr suggest that the original rocks were dunite or harzburgite, as this is also suggested by the rock relic texture. For forearc-mantle peridotites, it appears that they were hydrated by the water released from subducted slabs.